PERCEPTION MARKETING: HOW MARKET SATURATION INFLUENCES CREATIVITY AND THE FORMAT OF CONSUMER COMMUNICATION - Voloshko, Liudmyla (SWorldJournal, 2025)
The article examines how perception marketing adapts to the challenges of market saturation, influencing creativity and formats of consumer communication. The goal of the study is to explore how companies can effectively leverage creative approaches to ma